Potensi Pengembangan Minyak Atsiri Serai Wangi di Science Techno Park Kabupaten Trenggalek - Nurfitasari, Aditya; Supriyono, Supriyono; Mulyaningtiyas, Ratna Dewi (Universitas Islam Kadiri, 2024)
Citronella is an aromatic plant that is needed as a raw material in various industries so that aromatic plant commodities have high economic value. Science Techno Park is a unit that was built as an effort to downstream innovative academic and research products while acting as an epicenter for academic community innovation in various scientific fields, one of which is the development of citronella plants as an essential oil producing plant. . The citronella plant is a plant that is easy to cultivate and efforts to develop citronella are an effort to create competitive local products through the development of citronella plants and innovation in the development of citronella essential oil products. The research uses qualitative data analysis methods and calculates business feasibility using business feasibility analysis. Data collection in this research used primary data through interviews, observation and documentation as well as secondary data from various related sources. The results of data analysis show that the development of citronella plants in the Science Techno Park (STP) Trenggalek Regency started in 2018 in collaboration with the Brawijaya University, which is a university’s contribution in developing the community's economy through technology. It is hoped that the development of citronella plants produce an agricultural commodity that can become an icon of competitive local products. The development of citronella essential oil in the Science Techno Park (STP) has good potential to increase income in the Science Techno Park (STP). Apart from refining which produces essential oils, development can be directed at developing derivative products from citronella oil. Feasibility of a citronella essential oil refining business in the Science Techno Park (STP). Based on income calculations, it can be seen that the average total income obtained was Rp. 92,295,000, with an average expenditure for production costs of IDR 62,482,500, so that the citronella distilling business gets an average net income of IDR. 29,812,500, per year. And from calculating the R/C Ratio, the result is R/C ratio = 1.5, which means it is worth developing